Pendidikan Jiwa Generasi Z : Solusi Ibnu Sina atas Anxiety dari Perspektif Filsafat Islam - Alyaa‘Ulmuna; Nasikhin Nasikhin; Mustopa Mustopa (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Generation Z (born 1997–2012) in Indonesia experiences an increase in anxiety disorders due to social media pressure, academic stress, social isolation, and future uncertainty. Modern psychological approaches such as cognitive-behavioral therapy are widely used, but often do not involve the spiritual aspects that are important in Indonesian culture. This research aims to examine the handling of anxiety in Generation Z through the perspective of Islamic philosophy, especially the thought of Ibn Sina. The method used is a literature study with a qualitative descriptive approach. The results of the study show that Ibn Sina views mental health as a balance between body, soul, and intellect (vegetable, animal, and rational nafs). It offers a holistic approach that includes physical, mental, emotional, and spiritual therapies, such as art, music, prayer, and dhikr. This approach has the potential to help Generation Z deal with anxiety not only from a medical perspective, but also through strengthening the meaning of life and spirituality. The contribution of this research is to provide a philosophical framework that integrates modern psychological interventions with Islamic spiritual traditions, thereby offering a more culturally relevant approach to dealing with anxiety in adolescents.